MEMBEDAH SERVANT LEADERSHIP PERSONAL KEFARMASIAN (Sebuah Studi Kasus Apoteker PT. Kimia Farma Apotek UB Semarang) - Wisudasari, Ita Zonia; Mas'ud, Fuad; Rahardja, Eddy (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2017)
The purpose of this research is to analyze the characteristics of servant leadership and servant leadership competence conducted Apothecary built by the Apothecary at PT. Kimia Farma UB Semarang.From this research is expectedÂ to contribute the development of science in general and the field of human resources management in particular and as a reference when further research is conducted, especially on those who want to learn about servant leadership.Another goal is that managementÂ is expected to use as a material consideration or input to PT. Kimia Farma UB Semarang as a guide in competition Pharmacist to have leadership servant leadership that synergize with professionThe participants of this research consisted of 10 people, consisting of 7 (seven) person Apothecary and 3 (three) Apothecary Assistant. The ten participants representing structural position of PT. Kimia Farma UB Semarang. Determination of informants using snowball sampling method. This research method is qualitative analysis tool used is the technique of triangulation and member check.The result of the analysis showed that all participants of PT. Kimia Farma UB Semarang proved the characteristics of servant leadership and servant leadership competence can be built by the pharmacist. Expected Pharmacist as a leader able to build a communication that can synergize existing resources to maximize the potential of subordinates to be successful